2018
DOI: 10.1136/jmedgenet-2017-105145
|View full text |Cite
|
Sign up to set email alerts
|

XRCC2 mutation causes meiotic arrest, azoospermia and infertility

Abstract: BackgroundMeiotic homologous recombination (HR) plays an essential role in gametogenesis. In most eukaryotes, meiotic HR is mediated by two recombinase systems: ubiquitous RAD51 and meiosis-specific DMC1. In the RAD51-mediated HR system, RAD51 and five RAD51 paralogues are essential for normal RAD51 function, but the role of RAD51 in human meiosis is unclear. The knockout of Rad51 or any Rad51 paralogue in mice exhibits embryonic lethality. We investigated a family with meiotic arrest, azoospermia and infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…We used functional analysis to explore the effects of this mutation further. Firstly, total RNA was extracted from patients' blood, and reverse transcription PCR (RT‐PCR) showed this variant caused partially aberrant splicing (Figure D), consistent with the earlier report . In addition, immunofluorescence revealed that γH2AX staining appeared prominently in the spermatocytes undergoing preleptotene to zygotene in the seminiferous tubules of the male patient, and no sex body was observed (Figure E).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…We used functional analysis to explore the effects of this mutation further. Firstly, total RNA was extracted from patients' blood, and reverse transcription PCR (RT‐PCR) showed this variant caused partially aberrant splicing (Figure D), consistent with the earlier report . In addition, immunofluorescence revealed that γH2AX staining appeared prominently in the spermatocytes undergoing preleptotene to zygotene in the seminiferous tubules of the male patient, and no sex body was observed (Figure E).…”
supporting
confidence: 85%
“…These results suggested that spermatogenesis was blocked in the zygotene stage in our male patient. Furthermore, terminal dexynucleotidyl transferase(TdT)‐mediated dUTP nick end labeling (TUNEL) assay showed a significant increase in apoptotic germ cells in his seminiferous tubules, similar to Xrcc2 knock‐in mice (Figure F) …”
mentioning
confidence: 80%
See 1 more Smart Citation
“…These three genes are highly expressed in meiotic tissues in animals [2830] and plants [3133]. In humans, mutation in XRCC2 has been linked to meiotic arrest, azoospermia and infertility [34] and absence of RAD51B or RAD51D lead to meiotic defects in the moss Physcomitrella patens and rice, respectively [3537]. The Arabidopsis xrcc2 mutant and, to a lesser extent rad51b , have been associated with increased meiotic recombination rates, but all three mutants are fully fertile and present no detectable meiotic defects [24, 3840].…”
Section: Introductionmentioning
confidence: 99%
“…8 The incidence of genetic disorders in patients with MA is as high as 45%, as shown by chromosome analysis and Y chromosome microdeletion detection. 8 Monogenic [9][10][11][12][13][14][15][16] However, the genetic factors associated with the majority of MA cases remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%